Konflik Sosial dan Batin Tokoh dalam Novel Gadis Pantai Karya Pramoedya Ananta Toer Tinjauan Sosiopsikologi Sastra - Achmad, Noer Adhela Krisna Putri; Purnamasari, Hetty; Amrullah, Imron (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This research examines the novel Gadis Pantai (The Girl from the Coast) by Pramoedya Ananta Toer as a literary work that reflects social inequality and the oppression of women within the Javanese feudal system. The novel's strong feudal setting triggers various issues for its main character. This research aims to analyze two main focuses: (1) the forms of social conflict experienced by the main character, 'Ia', resulting from her social status, and (2) the forms of inner conflict she experiences as a psychological response to these pressures. This study utilizes a socio-psychological literary approach to uncover the intricate link between external social reality and the character's internal psychological dynamics. This study employs a descriptive qualitative method using library research (documentation) techniques. The analysis of social conflict is conducted by examining aspects of class inequality, patriarchal cultural norms, and power. Meanwhile, the analysis of inner conflict utilizes Sigmund Freud's psychoanalytic theory to dissect the personality dynamics of the id, ego, and superego within the main character, 'Ia'. The findings of this research are expected to provide an indepth explanation of how external social pressures (social conflict) directly shape and trigger the main character's psychological struggles (inner conflict), serving as a representation of social criticism against the oppressive feudal system.